Business process costs of implementing "gold" and "green" open access in institutional and national contexts. (26th June 2015) - Johnson, Robert; Pinfield, Stephen; Fosci, Mattia
Abstract : As open access (OA) publication of research outputs becomes increasingly common and is mandated by institutions and research funders, it is important to understand different aspects of the costs involved. This paper provides an early review of administrative costs incurred by universities in making research outputs OA, either via publication in journals ("Gold" OA), involving payment of article‐processing charges (APCs), or via deposit in repositories ("Green" OA). Using data from 29 UK institutions, it finds that the administrative time, as well as the cost incurred by universities, to make an article OA using the Gold route is over 2.5 times higher than Green. Costs are then modeled at a national level using recent UK policy initiatives from Research Councils UK and the Higher Education Funding Councils' Research Excellence Framework as case studies. The study also demonstrates that the costs of complying with research funders' OA policies are considerably higher than where an OA publication is left entirely to authors' discretion. Key target areas for future efficiencies in the business processes are identified and potential cost savings calculated. The analysis is designed to inform ongoing policy development at the institutional and national levels.